Critical thinking analysis of the perspective of Islamic education psychology study of teenager development - Lilis Patimah; Azka Aqiilah Nasywa (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The aim of research is critical thinking, an important tool to help students make responsible and rational decisions by understanding, analyzing, and evaluating the information they receive. Currently, adolescents' critical thinking skills are not optimal. They tend to be easily influenced by false or misleading information, receive information from social media or the internet without evaluating the truth, so they are vulnerable to hoaxes and propaganda. Teens tend to rely on instant solutions or follow the opinions of others without considering better alternatives. This can result in less effective decision-making and often does not consider future impacts. This study aims to analyze critical thinking from the perspective of Islamic educational psychology in adolescents, focusing on how adolescent development affects their critical thinking abilities. The research uses a qualitative approach and library research methods. The result of this study is that the development of critical thinking in adolescents is strongly influenced by various cognitive, emotional, and environmental factors that are the basis of Islamic educational psychology. A holistic and integrated approach to Islamic education can help facilitate critical thinking skills by emphasizing spiritual, moral, and ethical values in the learning process. In addition, support from family, school, and community also plays an important role in creating an environment conducive to the development of critical thinking skills. The study confirms that with the right approach, Islamic education can contribute significantly to developing critical thinking capacity in adolescents, which in turn will help them in facing life's challenges and becoming more thoughtful and reflective individuals.